2022
DOI: 10.3389/fimmu.2022.965224
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CD19-specific CAR-T cell-based therapy in secondary central nervous system lymphoma

Abstract: Encouraging response has been achieved in relapsed/refractory (R/R) B-cell lymphoma treated by chimeric antigen receptor T (CAR-T) cells. The efficacy and safety of CAR-T cells in central nervous system lymphoma (CNSL) are still elusive. Here, we retrospectively analyzed 15 patients with R/R secondary CNSL receiving CD19-specific CAR-T cell-based therapy. The patients were infused with CD19, CD19/CD20 or CD19/CD22 CAR-T cells following a conditioning regimen of cyclophosphamide and fludarabine. The overall res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The included studies were published between 2019 and 2023 and deemed relatively high quality ( Table 1 ). The meta-analysis analyzed the sustained efficacy of CAR T-cell therapy for a total of 69 patients with CNSL, who achieved an objective response [complete response (CR) or partial response (PR)], across 12 cohort studies ( Frigault et al, 2019 ; Li et al, 2020 ; Ahmed et al, 2021 ; Ghafouri et al, 2021 ; Roddie et al, 2021 ; Siddiqi et al, 2021 ; Wu et al, 2021 ; Frigault et al, 2022 ; Liu et al, 2022 ; Xue et al, 2022 ; Zhang et al, 2022 ; Lacan et al, 2023 ). These studies encompassed 27 PCNSL and 42 SCNSL, with sample sizes ranging from 2 to 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published between 2019 and 2023 and deemed relatively high quality ( Table 1 ). The meta-analysis analyzed the sustained efficacy of CAR T-cell therapy for a total of 69 patients with CNSL, who achieved an objective response [complete response (CR) or partial response (PR)], across 12 cohort studies ( Frigault et al, 2019 ; Li et al, 2020 ; Ahmed et al, 2021 ; Ghafouri et al, 2021 ; Roddie et al, 2021 ; Siddiqi et al, 2021 ; Wu et al, 2021 ; Frigault et al, 2022 ; Liu et al, 2022 ; Xue et al, 2022 ; Zhang et al, 2022 ; Lacan et al, 2023 ). These studies encompassed 27 PCNSL and 42 SCNSL, with sample sizes ranging from 2 to 14.…”
Section: Resultsmentioning
confidence: 99%
“…These studies encompassed 27 PCNSL and 42 SCNSL, with sample sizes ranging from 2 to 14. Patients underwent CAR T-cell monotherapy in six studies ( Frigault et al, 2019 ; Ahmed et al, 2021 ; Ghafouri et al, 2021 ; Roddie et al, 2021 ; Frigault et al, 2022 ; Zhang et al, 2022 ) and ASCT combined with CAR T-cell therapy in one study ( Wu et al, 2021 ), while diverse treatments containing CAR T-cell therapy were employed in the remaining five studies ( Li et al, 2020 ; Siddiqi et al, 2021 ; Liu et al, 2022 ; Xue et al, 2022 ; Lacan et al, 2023 ). For co-stimulation domains, two studies used CD28 ( Ghafouri et al, 2021 ; Siddiqi et al, 2021 ), six studies used 4-1BB ( Frigault et al, 2019 ; Roddie et al, 2021 ; Frigault et al, 2022 ; Liu et al, 2022 ; Xue et al, 2022 ; Zhang et al, 2022 ), two studies contained both CD28 and 4-1BB ( Ahmed et al, 2021 ; Lacan et al, 2023 ), and two studies used CD28/4-1BB ( Li et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“… 8 Several case studies have reported the efficacy and manageable adverse events of CAR-T therapy in primary and SCNSL, however in small, mostly single center cohorts and with short follow-up. 9 , 10 , 11 , 12 , 13 , 14 Duration of remission of SCNSL after CD19 CAR-T therapy has also been suggested to be shorter than that for patients without CNS involvement, 11 highlighting the need for longer follow-up.…”
mentioning
confidence: 99%